THE STUDY OF THE RELATIVE OPTICAL DENSITY OF BONE IN THE TREATMENT OF CHRONIC APICAL GRANULOMATOUS PERIODONTITIS - Жданова, Н.О. (World of Medicine and Biology, 2016)
The results were evaluated in arbitrary units of optical density and bone density compared with optical median section tooth root on one radiograph. As a result of determining the relative bone density area periapical expected rate of destruction.
Keywords: optical density; point of reference; the rate of destruction